A new monograph by Konstantin Frumkin [Review: Frumkin K.G. Admiring the Academic Class: Reflection of the Social History of Soviet Science in Literature, Art, and Public Rhetoric. Moscow, St. Petersburg, Nestor-Istoriya, 2022. (In Russian)] - D.E. Martynov; Yu.A. Martynova (Ученые записки Казанского университета: Серия Гуманитарные науки)
This article reviews a new monograph by K.G. Frumkin, an eminent culturologist and literary critic. He argues that the cult of science, as an institutionalized professional activity inseparable from the public interest in the work of scientists, is a specific feature of the 20th century. The ideological confrontation of the 1920s and 1930s touched little upon literature. In the fiction of that period, scientists were portrayed as inventors of fantastic military vehicles. After the 1950s, the relationship between scientific institutions and the state took a back seat in literature, while the relationship between scientists came to the fore. The scientific environment became self-sufficient. For the first time scientists were almost exclusively among colleagues, and the social circle they had outside their subculture shrank. The collective self-awareness of the scientific community was also taking shape. The author describes it as a “class mythology” characterized by undisguised elitism and “talent-centric racism.” The collapse of the USSR did not destroy Russian science, but the public enthusiasm for it practically dried up. A few literary works of that time referred to the past, both by rethinking and mythologizing it. The “admiration of the academic class” is thus a historically rooted phenomenon of the 20th century.